Quality assurance in melanoma care: guideline‐based quality indicators for melanoma – implementation, evaluation and update process. (23rd June 2020) - Follmann, Markus; Eigentler, Thomas; Adam, Henning; Wenzel, Gregor; Langer, Thomas; Wesselmann, Simone
Summary: Background: In 2018, an update of the German evidence‐based (S3) guidelines "Diagnosis, Therapy and Follow‐up of Melanoma" first issued in 2013 was published under the auspices of the German Guideline Program in Oncology. The update also included a revision of existing guideline‐based quality indicators (QIs). Patients and methods: Using a standardized multi‐step process, the guideline‐derived QIs were revised by a multidisciplinary, interprofessional working group based on the strong (level A) recommendations contained in the guideline update as well as on a systematic literature search for international indicators and on the outcomes of existing QIs as reported by certified German skin cancer centers. Results: Based on the original set of twelve guideline‐based QIs agreed upon in 2013, the working group developed an updated set containing nine indicators. Four QIs were kept unchanged; two were modified; two were removed; and three new QIs were added. Unlike 2013, the working group was now able to incorporate the outcomes of QIs previously implemented at the various skin cancer centers. Conclusions: Close cooperation between guideline group and certification commission allows for the implementation of guideline‐based QIs in cancer care. Measured outcomes form the basis for updating both the guidelines and the QI development process. They provide information about the care of cancer patients in a real‐world setting as well as on guideline adherence and the feasibility of QIs themselves. This is a dynamic process that can be described in a transparent manner and that requires regular updating.